2017
DOI: 10.1136/jclinpath-2017-204335
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection ofcfiAmetallo-β-lactamase-producingBacteroides fragilisby the combination of MALDI-TOF MS and CarbaNP

Abstract: The combination of MALDI-TOF MS and the CarbaNP assay can be applied in diagnostic clinical laboratory for rapid identification of with IS element-activated gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…The lengthy nature of conventional methods for bacterial identification and susceptibility testing purposes has resulted in the empirical use of broad-spectrum antibiotics and led to the spread of resistance [85]. Aiming at rapid and reliable detection of AMR, numerous studies have recently been reported on the use of ML algorithms in combination with the output of several analytical techniques, such as MALDI-TOF MS [89,96,[110][111][112][113][114][115][116][117][118], vibrational spectroscopy [102,103,119], whole-genome sequencing [120][121][122][123][124], a microscopy-based platform [125], and acousticenhanced flow cytometry [126].…”
Section: Detection Of Antimicrobial Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The lengthy nature of conventional methods for bacterial identification and susceptibility testing purposes has resulted in the empirical use of broad-spectrum antibiotics and led to the spread of resistance [85]. Aiming at rapid and reliable detection of AMR, numerous studies have recently been reported on the use of ML algorithms in combination with the output of several analytical techniques, such as MALDI-TOF MS [89,96,[110][111][112][113][114][115][116][117][118], vibrational spectroscopy [102,103,119], whole-genome sequencing [120][121][122][123][124], a microscopy-based platform [125], and acousticenhanced flow cytometry [126].…”
Section: Detection Of Antimicrobial Resistancementioning
confidence: 99%
“…Using an RF model on MALDI-TOF MS spectra, Huang et al [115] were able to correctly identify 93% of carbapenem-resistant and all carbapenem-sensitive Klebsiella pneumoniae isolates. Moreover, successful systems using a combination of MALDI-TOF MS data and ML algorithms were recently reported for the detection of extended-spectrum betalactamase-producing Escherichia coli (E. coli) strains [117], rapid detection of cfiA metallo-b-lactamase-producing Bacteroides fragilis strains [118], and identification of fluconazole resistance in Candida albicans strains [96].…”
Section: Detection Of Antimicrobial Resistancementioning
confidence: 99%
“…This approach has been successfully applied to Gram-negative bacteria, mycobacteria and to Staphylococcus aureus. The parallel use of MALDI-TOF MS and of a vector machine model as a supporting tool for the generation of a reliable algorithm (ClinProTools) has allowed the rapid identification of Bacillus fragilis and the differentiation of cfiA-positive and cfiAnegative subgroups [13].…”
Section: Antibiotic Resistance Determinationmentioning
confidence: 99%
“…Having antimicrobial resistance phenotyping at the time of MALDI-TOF measurement would eliminate this critical time delay. Previous work ( Ho et al , 2017 ; Mather et al , 2016 ; Sogawa et al , 2017 ) already recognized the potential of applying machine learning to MALDI-TOF mass spectra for antibiotic resistance prediction. However, the scope of these studies is limited by (i) relatively small numbers of spectra of often less than 100 isolates, (ii) the use of machine learning algorithms that are not specifically adapted to the application problem, and (iii) a focus on detecting single peaks (or small subsets of peaks) for the purpose of providing a full discrimination between resistant and susceptible samples.…”
Section: Introductionmentioning
confidence: 99%